LEGALITAS OPERASI TANGKAP TANGAN (OTT) KOMISI PEMBERANTASAN KORUPSI TERHADAP KORUPSI - Sinaga, Lestari Victoria; Simbolon, Nanci Yosepin; Hamonangan, Alusianto (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2022)
Operation Catch the Hand (OTT) is actually not known in the Criminal Procedure Code, this term contains the meaning of contradiction and confuses legal terms. In fact, it was an arrest operation because it had been preceded and sufficient preliminary evidence was found. The arrest operation carried out by the Corruption Eradication Commission is an effort to eradicate corruption through a secret operation by arresting the perpetrators while committing acts of corruption. This research method is normative juridical. The formulation of the problem studied is the regulation of hand arrest operations according to the legislation. Term caught in the hands in KUHAP and OTT in relation to the term controlled delivery. The result is that the implementation of OTT violates the rules in the Criminal Procedure Code. The Criminal Procedure Code stipulates several acts or coercive measures that can be carried out by limiting a person's freedom and independence on the grounds of having committed a criminal act.